RANCANG BANGUN DAN UJI TEKNIK KOMPOR BERBAHAN BAKAR LIMBAH BIOMASA PERTANIAN - Rahmad Hari Purnomo; Endo Argo Kuncoro; Dian Wahyuni (Universitas Tribhuwana Tunggadewi, 2014)
The research objective was to design and test of stove using agricultural waste biomass fuel. Engineering design was used in this research. The collected data was presented and tabular and graphical forms. This research was consisted of design, fabrication, technical test and perfomance analysis of stove which used agricultural waste biomass fuel. The observed parameters were combustion operational time, fuel consumption rate, specific gasification rate, combustion efficiency, heat energy input and ash percentage. Results showed that the highest combustion operational time was found on rice husk with magnitude of 0.43 hour and the lowest was found on wood chips with magnitude of 0.22 hour. The highest fuel consumption and gasification rates were found on wood chips with magnitude of 3.92 kg/h and 74.81 kg/m2h, whereas the lowest was found on rice husk with magnitude of 2.33 kg/h and 44.01 kg/m2h. The highest heat energy input value was found on wood chips with magnitude of 5,033.34 kcal, whereas the lowest was found on rice husks with magnitude of 3,411.29 kcal. The highest combustion efficiency was found on rice husk with magnitude of 4.67 % and the lowest was found on acacia leaves of 3.04 %. The highest ash percentage was found at rice husk with magnitude of 30 % and the lowest of 15 % was found on wood chips